Hyphal penetration is the major pathway of translocation of Candida albicans across the blood-cerebrospinal fluid barrier: brief report - Schmidt, S.; Schwerk, Christian; Schroten, Horst; Ishikawa, Hiroshi; Schubert, R.; Lehrnbecher, Thomas; Rudolph, Henriette (Fluids and barriers of the CNS, 2025)
Despite the availability of potent antifungal compounds, invasive fungal disease poses significant morbidity and mortality in immunocompromised patients. Candida albicans is one of the leading pathogens in this setting, and may affect the central nervous system (CNS), which is an extremely severe form of the infection. As the exact pathogenesis of Candida CNS infection is not clear, we investigated the mechanisms and effects of C. albicans transmigration into the CNS, which will be helpful for diagnosis, prevention and treatment. We used a human in vitro model of the Blood-Cerebrospinal Fluid Barrier (BCSFB), and we investigated the mechanisms of Candida albicans translocation into the CNS. Translocation was evaluated using immunofluorescence analysis focusing on tight and adherens junctions and the actin cytoskeleton. Barrier integrity was monitored via measurement of transepithelial resistance and the paracellular permeability of dextran. LIVE/DEAD assays were applied for viability controls and a cytometric bead array was performed to detect cytokine secretion of plexus epithelial cells. Translocation at low doses occurs transcellularly in the absence of cytotoxicity or secretion of proinflammatory cytokines. This is accomplished by the formation of a tunnel-like structure exploiting the actin cytoskeleton. With higher infection doses of Candida albicans, a reduction in barrier integrity due to disruption of tight and adherens junctions was observed and cytotoxicity also increased. Our findings reveal that Candida albicans can use transcellular translocation to invade into the CNS and is able to circumvent major host immune response, which may impact on diagnostic and preventive strategies.